Cernunnos/XLF Deficiency: A Syndromic Primary Immunodeficiency - Funda Erol Çipe; Cigdem Aydogmus; Arzu Babayigit Hocaoglu; Merve Kilic; Gul Demet Kaya; Elif Yilmaz Gulec (Case Reports in Pediatrics)
Artemis, DNA ligase IV, DNA protein kinase catalytic subunit, and Cernunnos/XLF genes in nonhomologous end joining pathways of DNA repair mechanisms have been identified as responsible for radiosensitive SCID. Here, we present a 3-year-old girl patient with severe growth retardation, bird-like face, recurrent perianal abscess, pancytopenia, and polydactyly. Firstly, she was thought as Fanconi anemia and spontaneous DNA breaks were seen on chromosomal analysis. After that DEB test was found to be normal and Fanconi anemia was excluded. Because of that she had low IgG and IgA levels, normal IgM level, and absence of B cells in peripheral blood; she was considered as primary immunodeficiency, Nijmegen breakage syndrome. A mutation in NBS1 gene was not found; then Cernunnos/XLF deficiency was investigated due to clinical similarities with previously reported cases. Homozygous mutation in Cernunnos/XLF gene (NHEJ1) was identified. She is now on regular IVIG prophylaxis and has no new infection. Fully matched donor screening is in progress for bone marrow transplantation which is curative treatment of the disease. In conclusion, the patients with microcephaly, bird-like face, and severe growth retardation should be evaluated for hypogammaglobulinemia and primary immunodeficiency diseases.